1967
DOI: 10.1017/s0010417500004540
|View full text |Cite
|
Sign up to set email alerts
|

Tradition and Modernity Reconsidered

Abstract: Modernization is a term which became fashionable after World War II. It is useful despite its vagueness because it tends to evoke similar associations in contemporary readers. Their first impulse may be to think of “the modern” in terms of present-day technology with its jet-travel, space exploration, and nuclear power. But the common sense of the word “modern” encompasses the whole era since the eighteenth century when inventions like the steam engine and the spinning jenny provided the initial, technical bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
1
6

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(48 citation statements)
references
References 10 publications
0
41
1
6
Order By: Relevance
“…As stated by Bendix, 'what is true of all traditional societies is by the same token not very illuminating about any one of them'. 59 Hybridity in societies has been well illustrated by Robins in the case of Kalahari San identity; he also details the discomfort of many development actors vis-a-vis hybrid societies, and how the 'Western versus traditional Bushmen' dichotomy in NGOs and donor discourses contributed to divisions and conflicts within the community. 60 The difficulty of Western observers to accept either hybridity or simply social change in Indigenous societies is perfectly summarised by Sahlins using Margaret Jolly's work on inauthenticity: 'When we change it's called progress, but when they do -notably when they adopt some of our progressive things -it's a kind of adulteration, a loss of their culture'.…”
Section: It Is Irrelevantmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by Bendix, 'what is true of all traditional societies is by the same token not very illuminating about any one of them'. 59 Hybridity in societies has been well illustrated by Robins in the case of Kalahari San identity; he also details the discomfort of many development actors vis-a-vis hybrid societies, and how the 'Western versus traditional Bushmen' dichotomy in NGOs and donor discourses contributed to divisions and conflicts within the community. 60 The difficulty of Western observers to accept either hybridity or simply social change in Indigenous societies is perfectly summarised by Sahlins using Margaret Jolly's work on inauthenticity: 'When we change it's called progress, but when they do -notably when they adopt some of our progressive things -it's a kind of adulteration, a loss of their culture'.…”
Section: It Is Irrelevantmentioning
confidence: 99%
“…61 Also, the adoption of modern practices should not be mistaken with a complete endorsement of modern society, and as stated by Bendix, 'modernization in some sphere of life may occur without resulting in 'modernity''. 62 It has also been identified that there are actually several Modernities. Lee argues that the challenges posed to modernity by postmodernism in the 1980s has actually not led to its collapse; instead, it has in a sense 'rebounded' through the emergence of new terms, such as 'reflexive modernity' (Giddens and Beck), 'liquid modernity' (Bauman) and 'multiple modernities'.…”
Section: It Is Irrelevantmentioning
confidence: 99%
“…The point to be emphasized here, however, is that the referent of "social" was almost invariably the communal. Communitas, not societas with its more impersonal connotations, is the real etymological source of the sociologist's use of the word "social" in his studies of personality, kinship, economy and polity (Nisbet 1967: 56, my italics) Apart from Tönnies's original formulation, this rendition is also far from Durkheim's (1984) argument in Division of Labour or Reinhard Bendix's (1967) rendition of it in terms of 'tradition' and 'modernity'. As a historical transition, Nisbet associated the movement from Gemeinschaft to Gesellschaft to questions of rapid social change that had in fact become the theoretical backbone to modernisation approaches in the social sciences of the 1950s and 1960s.…”
Section: IImentioning
confidence: 99%
“…Západě. Příkladem může být, že vývoj v západní Evropě po roce 1492 přetrvává jako tradiční předmět sociologických studií už od časů klasických sociologů [Bendix 1967]. Historicky orientovanou sociologii, jakou já mám na mysli, je možno najít například v pracích W. G. Runcimana [1989Runcimana [ , 2004Runcimana [ , 2009, Jacka Goodyho [1996,2004,2007,2009] a Michaela Manna [1986,1993].…”
unclassified